Corrigendum: Embedded remote group environment through modification in MACBETH - an application of contractor’s selection in construction - Khoso, Ali Raza; Yusof, Aminah Md; Chen, Zhen-Song; Wang, Xian-Jia; Skibniewski, Mirosław J.; Memon, Nafees Ahmed (Journal of Civil Engineering and Management, 2022)
Ali Raza Khoso, Aminah Md Yusof, Zhen-Song Chen, Xian-Jia Wang, Mirosław J. Skibniewski, Nafees Ahmed Memon, authors of the article “Embedded remote group environment through modification in MACBETH – an application of contractor’s selection in construction”, published in Journal of Civil Engineering and Management, 27(8), 595–616, https://doi.org/10.3846/jcem.2021.15763 inform that several errors occur in affiliations. The correct affiliation of the first author Ali Raza Khoso should be 1) Department of Structure and Materials, School of Civil Engineering, Faculty of Engineering, Universiti Teknologi Malaysia, Johor Bahru, Malaysia and 2) Department of Civil Engineering, Mehran University of Engineering & Technology, Jamshoro, Pakistan. The correct affiliation of the second author Aminah Md Yusof should be 1) Department of Structure and Materials, School of Civil Engineering, Faculty of Engineering, Universiti Teknologi Malaysia, Johor Bahru, Malaysia. The authors regret this error and would like to apologize for any inconvenience caused.